(untitled) (Comparative Professional Pedagogy, 2025)
This article emphasizes the relevance of developing analytical competence of future economists at the current stage of educational reform. The author emphasizes the importance of a modern specialist’s ability to analyze information, identify cause-and-effect relationships, critically evaluate data, and substantiate conclusions in all areas of activity (science, business, education, management, and engineering). This work also highlights the importance of studying the world’s experience in developing the analytical competence of economists, as this provides domestic teachers of economic disciplines with a basis for building targeted learning and developing innovative methods for developing critical thinking and analytical skills in future specialists. The author outlines the spectrum of problems in developing analytical competence of economists in foreign countries and notes the widespread use of an interdisciplinary approach to the study of analytical competence of economists abroad, which allows for a deeper understanding of economic phenomena. The main aspects under the study are identified as follows: the development of professional analytical skills in economics; mathematical modeling and statistical analysis in analytical activity; the impact of automation on the effectiveness of economists’ analytical work; the study of the ability of economists to holistically perceive economic processes; motivation for analytical activity; and the impact of personal qualities on the ability to perform analytical work. These very aspects reflect the multifaceted nature of approaches to studying the analytical competence of economists. It should be noted that the relevance of developing analytical skills among economists is currently being reinforced by trends toward humanization and humanities-oriented approaches in higher education. The conclusions of this work indicate that the desire to increase the level of analytical competence remains a key area of ​​training economists in foreign countries and is carried out not only through academic educational programs, but also through independent scientific research.